Obesidade em discurso: o corpo gordo no Facebook - Aguiar, Fernanda Bevilacqua de (2020)
This research seeks to investigate the discourses that address obesity and the fat body in social media, specifically Facebook. The research corpus contemplates the selection of ten pages related to obesity and the portrait of fat bodies through the time of a year, between July 2018 and August 2019. To study the role of obesity in the development of body ideals through capitalist logic and promote the analysis of the chosen Facebook pages, the input of Ernest Laclau and Chantal Mouffe discourse theories were fundamental, as to identify the hegemonic and antagonistic relations between the discourses. For the theatrical fundament, were harnessed the works of Georges Vigarello, Denise Sant’Anna, and Jean-Pierre Poulain, to explain the concepts of beauty and production of the self through standards that value the image and slim body type exposure, in search of the esthetic perfection. These concepts were also studies with the support of authors as José Luiz Aidar Prado, David Le Breton, and Isleide Fontenelle. To understand the influence and the power of medicine in a media context that supports the health and well-being, that was vital to comprehend the concepts described by Nikolas Rose. Provide this study was possible to analyze better the different Facebook discourses that are articulated about obesity, as the relations established about them, to comprehend and question the construction of the image of fat people online